Assessing the residential and schools’ surrounding environments for child-friendliness in precinct 11 Putrajaya, Malaysia - HABSAH HASHIM; SITI FATIMAH HASHIM; YUSFIDA AYU ABDULLAH; NA’ASAH NASRUDIN (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The purpose of this research is to assess the proximity of homes and schools in terms of their child-friendliness using a variety of indicators. The idea of creating sustainable urban and community environments is central.Method: Using the Analytical Hierarchy Process (AHP) and a case study approach, it promotes livability by adhering to basic human needs. Primary data were collected through in-person observations of sites, including examining site characteristics, taking photographs of the surrounding environment and its elements, and examining the children’s movement patterns. Tracking the whereabouts of elementary school kids was also a part of the investigation.Findings: Research shows that neighbourhoods near schools are accommodating to students’ needs. Signage, playground equipment, and pedestrian walkways were found to all contribute to a more kid-friendly setting. The research also found that several contextual factors, such as proximity to pedestrian amenities and the entrance to a school, influence how child-friendly a given area is.Implications/Novel Contribution: The study added to the growing body of evidence suggesting that child friendly indicators be incorporated into residential planning to improve the quality of life for children in urban areas.